Vancomycin-Resistant Bacillus cereus Pneumonia and Bacteremia After Nonfatal Freshwater Drowning - Deepthi Nacharaju; Asa Tapley; Ellora N. Karmarkar; Ferric C. Fang; Nicholas J. Johnson (Annals of Internal Medicine: Clinical Cases)
Bacillus cereus, a gram-positive rod commonly found in natural environments, is often presumed to be a contaminant or associated with toxin-mediated gastrointestinal disease. Bacillus cereus rarely causes severe invasive infections. Here we describe the case of a previously healthy young man who had a nonfatal drowning incident in a freshwater lake, which resulted in acute respiratory distress syndrome requiring venovenous extracorporeal membrane oxygenation. He subsequently developed vancomycin-resistant B cereus pneumonia and bacteremia and died of complications of his disease. Bacillus cereus should be considered as a potential pathogen when repeatedly isolated from normally sterile sites, particularly in critically ill patients.